RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE TOWARDS THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) IN BUS MECHANICS AT PT. INTER CROSS SUMATRA - Maulidya Permata; Yulia Khairina Ashar; Reni Agustina Harahap (RADJA PUBLIKA, 2025)
This study aims to determine whether knowledge has a positive and significant effect on the use of PPE on bus mechanics at PT Antar Lintas Sumatra. This study uses two independent variables, namely knowledge and attitude with one dependent variable, namely the use of PPE. The type of data used in this study is primary data, where the data comes from the results of distributing questionnaires to bus mechanics at PT Antar Lintas Sumatra. After conducting a literature and field review and formulating a hypothesis, the population and sample in this study were 30 respondents, with a total sampling technique. This type of research is quantitative analytic with a cross-sectional approach. The research was conducted at the central workshop of PT Antar Lintas Sumatra in the period December 2024-March 2025. The research instrument used a closed questionnaire in the form of a Likert scale that had been tested for validity and reliability. Data analysis was carried out with software through multiple linear regression, as well as the t test and F test to test the relationship between variables, with the coefficient of determination (R²) to see the magnitude of the influence of the independent variable on the dependent variable. The t test shows that the knowledge variable (X1) has a significant effect on the use of PPE. This is proven by the results of the t-test statistics for the knowledge variable indicated by a value of 3.518 and in the table of 2.048 and a Sig value (0.002 <0.05). The attitude variable (X2) has a significant effect on the use of PPE. This is proven by the results of the t-test statistics for the attitude variable which is shown with a value of 12.188 and in the table of 2.048 and a Sig value (0.000 <0.05). The F test shows that the variables of knowledge (X1) and attitude (X2) have a significant effect on the use of PPE simultaneously. The coefficient of determination shows that 86.0% of PPE use is influenced by knowledge and attitude variables, and the remaining 14.0% by other variables not examined. Suggestions in this study are that companies must be able to provide PPE according to standards, tighten supervision of PPE use, and increase socialization of PPE use in the work environment.